Doseganje književnovzgojnih ciljev z informacijsko-komunikacijsko tehnologijo v gimnaziji - Čampelj, Renata (Jezik in slovstvo, 2014)
Bringing together both quantitative and qualitative methodological research paradigms, our analysis combines experimental and action research based on two grammar school (gimnazija) classes. The experiment was carried out in two phases, each involving approximately three weeks of distance learning project work, with the control group and the experimental group taking turns in each phase. The first experimental phase included distance learning by means of technology, classic textbook and workbook, while the second phase only involved work in an Internet classroom. Tests and questionnaires were used as measurement instruments. By adopting this combination of research methods, we confirmed our initial hypothesis that literary educational goals (literary competence, literary knowledge and educational goals) can be achieved with equal success both by classic teaching methods and contemporary approaches.
Keywords: didaktika književnosti; književnovzgojni cilji; učnje na daljavo; eksperimenti; informacijsko komunikacijska tehnologija; gimnazije